1980
DOI: 10.1148/radiology.136.1.6446106
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-hydroxymethane diphosphonate: a new bone imaging agent with a low tin content.

Abstract: A prospective double-blind comparison of 99mTc-hydroxymethane diphosphonate (HMDP) and 99mTc-methylene diphosphonate (MDP) as bone-seeking agents was performed with 102 patients. Densitometry showed that both cancellous/compact bone and cancellous bone/soft-tissue ratios were greater with HMDP (p less than 0.05); compact bone/soft-tissue and bone lesion/normal bone ratios were the same with both agents. Bone delineation, soft-tissue uptake, and overall image quality were the same with both agents. The HMDP for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…DOTA-Bn-SCN-HBP (3) as a precursor was synthesized by a Ogawa et al 13/35 coupling reaction between p-SCN-Bn-DOTA (1) and alendronate (2) according to Scheme 1. 67 Ga labeling was performed by complexation between DOTA-Bn-SCN-HBP or DOTA and 67 Ga.…”
Section: Preparation Of 67 Ga-labeled Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…DOTA-Bn-SCN-HBP (3) as a precursor was synthesized by a Ogawa et al 13/35 coupling reaction between p-SCN-Bn-DOTA (1) and alendronate (2) according to Scheme 1. 67 Ga labeling was performed by complexation between DOTA-Bn-SCN-HBP or DOTA and 67 Ga.…”
Section: Preparation Of 67 Ga-labeled Compoundsmentioning
confidence: 99%
“…Over the last thirty years, complexes of 99m Tc with bisphosphonate, such as methylene diphosphonate ( 99m Tc-MDP) and hydroxymethylene diphosphonate ( 99m Tc-HMDP), have been widely used as radiopharmaceuticals for the imaging of bone disorders such as metastatic bone disease, Paget's disease, osteoporotic fractures, etc [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…After introduction of 99m Tc-methylene diphosphonate (MDP, Figure 1(c)) by Subramanian et al [11] in 1975 and 99m Tc-hydroxymethylene diphosphonate (HMDP, Figure 1(d)) by Bevan et al [12] in 1980, 99m Tc-MDP, and 99m Tc-HMDP, which showed superior biodistribution compared to 99m Tc-HEDP, have been used as radiopharmaceuticals for bone scintigraphy for over thirty years [1315]. 99m Tc-MDP is postulated to form a bidentate-bidentate bridge with hydroxyapatite while the presence of the hydroxyl group in 99m Tc-HMDP would convert the ligand to form a bidentate-tridentate bridge and is expected to enhance the hydroxyapatite affinity of the 99m Tc complex [12, 16].…”
Section: 99mtc-bisphosphonate Complexesmentioning
confidence: 99%
“…A variety of 99m Tc-based radiopharmaceuticals have been developed and approved by the Federal Drug Administration (FDA) for determining organ function or assessing disease status by imaging methods [5][6][7]. Bone imaging agents are among the first developed 99m Tc-based radiopharmaceuticals and among the most widely used radiopharmaceuticals in the diagnostic nuclear medicine [7], which involve the coordination of 99m Tc to diphosphonates such as methylenediphosphonate (MDP) [8] and hydroxymethylenediphosphonate (HMDP) [9]. They have been widely used as radiopharmaceuticals for bone scintigraphy in cases of metastatic bone disease, Paget's disease, osteoporosis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely used as radiopharmaceuticals for bone scintigraphy in cases of metastatic bone disease, Paget's disease, osteoporosis, etc. [8][9][10][11][12]. With these 99m Tc-labeled diphosphonates (DPs), however, an interval of 2-6 h is needed *Author for correspondence (E-mail: jglin@yahoo.cn).…”
Section: Introductionmentioning
confidence: 99%